2010
DOI: 10.1111/j.1440-1843.2010.01713.x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical mask placement over N95 filtering facepiece respirators: Physiological effects on healthcare workers

Abstract: Use of a surgical mask as an outer barrier over N95 filtering facepiece respirators does not significantly impact the physiological burden or perceptions of comfort and exertion by the wearer over that experienced without use of a surgical mask.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
325
5
22

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(404 citation statements)
references
References 25 publications
23
325
5
22
Order By: Relevance
“…Interestingly, there was only one subject who mentioned the presence of moisture, a characteristic that has been reported as a major deterrent to respirator use. (22) This tends to agree with observations from the Roberge et al (23) study that found only minimal moisture (∼0.10 g) was retained on an N95 FFR after a subject's walking on a treadmill for an hour while wearing a respirator. However, given that the subjects only wore the FFR for ∼ 30 min in this study, this finding may not be surprising.…”
Section: Discussionsupporting
confidence: 78%
“…Interestingly, there was only one subject who mentioned the presence of moisture, a characteristic that has been reported as a major deterrent to respirator use. (22) This tends to agree with observations from the Roberge et al (23) study that found only minimal moisture (∼0.10 g) was retained on an N95 FFR after a subject's walking on a treadmill for an hour while wearing a respirator. However, given that the subjects only wore the FFR for ∼ 30 min in this study, this finding may not be surprising.…”
Section: Discussionsupporting
confidence: 78%
“…Arising from the difference of breathing resistance, lower heart rate was observed among the group wearing surgical masks than those wearing N95 masks (Li et al, 2005). In addition, it was also shown that N95 FFR dead-space has higher carbon dioxide and lower oxygen levels than the ambient workplace standards, respectively (Roberge et al, 2010). In developing more comfortable respiratory masks, an exhalation valve on the N95 respirator is being adopted and is shown not to affect the respiratory protection, while contributing to reducing the breathing resistance (Lee et al, 2008).…”
mentioning
confidence: 85%
“…Data collected showed that dead-space CO 2 ranged from 2.5-3.5% CO 2 which is significantly above OSHA's ambient workplace standards. Roberge et al (2010) concluded that even though the RPD did not impose any significant physiological burden on participants, CO 2 retention was a possibility due to elevated transcutaneous CO 2 (equivalent to arterial CO 2 ) levels. On a similar note, although no symptoms of CO 2 retention were recorded in this study, the increases in CO 2 during speech were sufficient enough to impact the participant.…”
Section: Discussionmentioning
confidence: 99%